Associação dos fatores de risco para a síndrome metabólica em escolares obesos e sobrepesos com idade de 6 a 10 anos do munícipio de Ouro Preto, MG - Joyce Andrade Batista (2010)
Obesity, the chronic disease that endangers the health of children and adolescents, emerges as a high prevalent condition worldwide, representing faithfully the imbalances of our time, combining organic, environmental, psychological, physiological and nutritional factors. Childhood obesity is an important public health concern because of its prevalence and consequences on the expectations and quality of life. It has many organic implications, emphasizing the metabolic syndrome, whose understanding has been permeated by challenges and progress. The metabolic syndrome, a complex worrying condition and with a controversial definition, has been outstanding among the implications of the obesity in childhood and adolescence, it increases the interest and frightens by the possibility of early lesions of atherosclerosis in the first decades of life. The instability of the diagnosis of the metabolic syndrome in pediatric patients has been put into evidence, discussing the necessity of making the diagnosis, and demanding, therefore caution. Due to few studies that follow up individuals from childhood to adulthood, little is known about how well the metabolic syndrome in pediatric patients predicts disease in adulthood. Given the lack of solid cut-off points in pediatric patients, the relationship between individual risk factors and their grouping in the process of atherosclerosis is difficult to define. The link between the obesity, the cardiovascular disease and the metabolic syndrome is a condition as complex as interesting, and it has increased the interest and the concern of many professional groups and sectorial and government agencies that deal with health.